Tax‐Induced Intertemporal Restrictions on Security Returns - BOSSAERTS, PETER; DAMMON, ROBERT M. (Journal of Finance, 1994)
ABSTRACT This article derives testable restrictions on equilibrium asset prices when investors have the option to time the realization of their capital gains and losses for tax purposes. The tax‐timing option alters both the magnitude and timing of equity returns relative to those in a tax‐free model. The tax‐induced restrictions are empirically examined, and the tax rates and preference parameters are estimated. While the tax‐free model can be rejected in favor of the tax‐based model as the specified alternative, the tax‐based model is still unable to adequately explain cross‐sectional differences in asset returns.